Portraying Theatre Locations in Kuala Lumpur, Malaysia: Transportation Accessibility for the Public - Walid, Ali; Syahrul Fithri, Musa; Mohd Saad, Omar; Muhammad Faisal, Ahmad; Atta Idrawani, Zaini (Semarak Ilmu Publishing, 2024)
The city centre of Malaysia is a key location for theatre and performing arts, drawing in a large audience. Venues like Istana Budaya, which hosts the National Musical of Malaysia, feature modern technology and unique performance styles. They are venues with diverse audience members from various economic groups. Marketing for performances in Istana Budaya is easier compared to other venue with the status of Malaysia’s National Theatre in addition to the its strategic location that has efficient public transport access; walkable nearby train station. Some other venues has limited public transport options. As an alternative, the audience members attending shows using taxis or e-hailing services. The research is analysing on public transportation accessibility focusing on train locations. Previous research on performing arts impact and its relationship with public transportation location - considering characteristic of the audience members, sustainability, and space specification in order for mapping the performing arts space in Klang Valley.